THE ANALYSIS OF INCUBATION TO THE START UP IN TERMS OF SALES REVENUE, JOB CREATION, INITIAL CAPITAL AND START UP AGE WITH THE NON-INCUBATION START UP - Kireyna Rahmah (Syntax Idea, 2020)
Currently the development of new business in Indonesia is growing rapidly alongside with the development a technology. The development of new business or what we called start up also effect to the development of many incubation program especially in Bandung city as the place where creativity began. This incubation program expect to help a new business to receive a support and guidance as they enter their market in order to have a good productivity. This study aims to determine the effect of incubation program toward the start up in terms of sales revenue growth, job creation, initial capital and start up age. Whether there is differences between incubated and non-incubated start up. Research method that being used is quantitative, based on the type of analysis that being used. The type of analysis that being used in this research is descriptive, in processing using descriptive test in order to analyze data. The population that being used in this study is start up that located in Bandung city, where the total sample in this study is 10 start up. This study uses Mann-Whitney U Test in order to analyzed the data Based on research results and discussion, there is differences between incubated and non-incubated start up in terms of sales revenue growth, job creation, initial capital, and start up age. The incubated start up have higher sales revenue growth, more lower number of employees, has lower initial capital and were younger than non-incubated one. Despite the differences, the Mann-Whitney U Test shown that the differences of them is not meaningful